Framework for Big Data integration in e-government - Diana Martinez-Mosquera; Sergio Luján-Mora (Dyna, 2019)
This article describes researches regarding Big Data integration in e‑government decision‑making, for instance, in areas like solar energy provisioning, environmental protection, agricultural and natural resources exploitation, health and social care, education, housing and transportation management, among others. These studies refer to regions that have integrated Big Data in e‑government, where South America is still in the early adoption stages. Hence, this study proposes three steppingstones for Big Data integration in e‑government decision‑making, production, management and application. The proposed framework aims to be a reference in South America for Big Data adoption in e‑government and thus help to mitigate the technology delay regarding other regions. Finally, a case study with open data obtained from the Instituto Nacional de Estadística y Censos of Ecuador (Ecuadorian Statistics and Census Agency) is presented.